Spatiotemporal Ultrafast-Plasmon Control Based on Response Functions of Nanostructures Measured by Interferometric Cross-Correlation Microscopy - Kusaba Miyuki; Onishi Shutarou; Kannari Fumihiko; Oi Jun (EPJ Web of Conferences, 2013)
We demonstrate an electrical-field cross-correlation imaging technique to obtain a response function of localized plasmon generated by femtosecond laser pulses on gold nanostructures. Based on the measured response functions, we spatiotemporally control the plasmon by shaping the femtosecond excitation laser pulses.